Anesthesiology : Clinical Case Reviews - Aglio, Linda S.; Urman, Richard D. (Springer International Publishing : Imprint: Springer, 2017)
Divided into twelve sections that cover the entirety of anesthetic practice, this is a case-based, comprehensive review of anesthesiology that covers the basics of anesthetic management and reflects all new guidelines and recently developed standards of care. Each chapter of Anesthesiology: Clinical Case Reviews begins with a specific clinical problem or a clinical case scenario, followed by concise discussions of preoperative assessment, intraoperative management, and postoperative pain management. In addition to residents and fellows, this book is written for practicing anesthesiologists, student nurse anesthetists, and certified registered nurse anesthetists (CRNAs).
Keywords: Medicine.; Anesthesiology.; Critical care medicine.; Pain medicine.; elektronické knihy; electronic books